Contrasting anion recognition behaviour exhibited by halogen and hydrogen bonding rotaxane hosts1. Issue 9 (7th March 2015) - Cornes, Stuart P.; Davies, Charles H.; Blyghton, David; Sambrook, Mark R.; Beer, Paul D.
<x xml:space="preserve">Abstract</x> A [2]rotaxane anion host that switches selectivity from dihydrogen phosphate to the halides upon substituting a hydrogen bond donor group for a halogen bond donor group within the axle component is described.